Growth Performance and Nutrient Utilization of Male Broiler Chicken as Affected by Feed Restriction with or without Garlic Supplementation - Singh, Vishavdeep; Singh, Udeybir; Sethi, A.P.S.; Lamba, J.S. (Indian Journal of Animal Nutrition, 2019)
An experiment was conducted to study the effects of feed restriction and garlic supplementation on growth performance weekly and nutrient utilization in male broilers. In this study, 120, day old male broilers were randomly distributed into 5 treatments each having 4 replicates with 6 birds in each replicate. Diets were formulated as per ICAR 2013 specifications and were fed in 3 phases. Treatment T1 was served as control. The other treatments comprised: T2 = T1 with feed restriction (10-12 h) at 8-17 days of age (DOA) with garlic supplementation, T3 = T1 with feed restriction at 8-17 DOA (10-12 h) without garlic supplementation, T4 = T1 with feed restriction at 18-27 DOA (10-12 hrs) with garlic supplementation, T5 = T1 with feed restriction at 18-27 DOA (10-12 hrs) without garlic supplementation. Early feed restriction (8-17 DOA) with or without garlic supplementation reduced (P<0.05) the average body weight gain at 2nd week of age. Garlic supplementation and late feed restriction from 18-27 DOA reduced (P<0.05) the average body weight gain at 4th week of age. Significantly reduced feed intake was observed in early feed restriction with garlic (T2) and without garlic (T3) at 2nd week of age and late feed restriction with garlic (T4) and without garlic (T5) at 4th week of age. Feed restrictions with or without garlic supplementation reduced the feed intake. There was no significant effect on feed conversion ratio (FCR) of early and late feed restriction with or without garlic supplementation expect at 5th week of age where FCR was observed to be better (P<0.05) in T2 and T4 as compared to control. There was no significant difference in protein efficiency ratio (PER) and calorie efficiency ratio (CER) due to early and late feed restriction with or without garlic supplementation in different weeks of age from 1st to 5th week of age. Early and late feed restrictions with garlic supplementation (T2 and T4) had significantly (P<0.05) higher digestibility of crude protein and organic matter. It was concluded that garlic supplementation irrespective of restriction period (early or late) improved the FCR at the 5th week of age, crude protein digestibility and organic matter digestibility.